Encyclopedia of applied developmental science - Fisher, Celia B.; Lerner, Richard M.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2005)
'Encyclopedia of Applied Developmental Science' is an authoritative source that encompasses the entire range of concepts involved in the study of applied developmental science.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child development -- Encyclopedias; Youth development -- Encyclopedias; Adolescence -- Encyclopedias; Developmental psychology -- Encyclopedias; Community development -- Encyclopedias; Electronic books